VAIZDUOTĖS AUTONOMIJA IR ESTETINĖ PATIRTIS. - Jonkus, Dalius (Problems / Problemos, 2016)
The paper discusses the modern idea of imagination and its various transformations in the phenomenological conceptual frameworks of Edward Casey, Mikel Dufrenne and Vasily Sesemann. I would like to raise and critically assess questions regarding the role of imagination in our consciousness: whether imagination is a productive or reproductive activity; and how, if at all, aesthetic expression limits imagination. Casey criticizes Dufrenne for his attempt to unite imagination with aesthetic expression. He argues for the autonomy of imagination, but leaves the question of the relationship between imagination and perception unanswered. Dufrenne partially shares his theory of imagination with Sesemann. Both philosophers claim that imagination is a reproductive activity rather than a productive one in the sense that it is limited by the forms of the material a priori. In other words, aesthetic expression has to obey the principle of correlation between percipiens and perceptum. Creativity becomes possible when the creator is able to reproduce in his expression another subject's possible perceptivity. Sesemann accentuates the primacy of embodied imagination in his aesthetics. He believes that the necessary correlation between the object and the subject is born in the movement of embodied imagination. The fact that imagination is an embodied phenomenon is illustrated by the way it exists in the world, since imagination is essentially a free activity restricted only by "the style of the world's horizon."